1987
DOI: 10.1093/jac/20.5.759
|View full text |Cite
|
Sign up to set email alerts
|

A survey of antibiotic outpatient prescribing and antibiotic self-medication

Abstract: In order to assess patterns of antibiotic prescribing and self-medication, a survey was carried out of patients from Government and private hospitals (500 each) and of 1000 apparently healthy adults in Benin City, Nigeria. Ampicillin and tetracycline were the antibiotics commonly used for self-medication; the commonest reasons given for the self-medication were the treatment of sexually transmitted diseases, cough, stomach upsets and diarrhoea. Ampicillin was the commonest prescribed antibiotic; the commonest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
5
16
0
Order By: Relevance
“…In contrast to studies in developing countries, this study identified few cases of self-medication for sexually transmitted diseases ( 34 , 35 ). Only 2 respondents in Lithuania reported self-medication for "gynecological infection" that might have been a sexually transmitted infection.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast to studies in developing countries, this study identified few cases of self-medication for sexually transmitted diseases ( 34 , 35 ). Only 2 respondents in Lithuania reported self-medication for "gynecological infection" that might have been a sexually transmitted infection.…”
Section: Discussionmentioning
confidence: 60%
“…However, it was not possible, from the approach we adopted, to establish whether the use of antibiotics in this study was inappropriate, as further studies involving laboratory and/or clinical data would be needed. However, antibiotics usage in the health facilities may have been inappropriate as observed in previous studies 34,35 .…”
Section: Drug Prescribing Patternmentioning
confidence: 85%
“…However, an over and/or an inappropriate use of antimicrobial agents has the potential to lead to the development and the spread of resistant strains of pathogens [8]. With this state of affairs of the antimicrobials, we planned to study the antimicrobial agents which were prescribed and administered to the patients who were admitted in the Medicine Department of Teerthanker Mahaveer Medical College Out of the 494 drugs which were prescribed to the patients, 291 were antibiotics.…”
Section: Pharmacology Sectionmentioning
confidence: 99%